Investigation of anti -nociceptive activity of Zingabeel (Zingiber officinale) on acetic acid induced writhing in rats - Awad, Enas M; Ahmed, Elhadi M Mohamed; El-hadiya, Tarig M. Hashim (Gezira Journal of Health Sciences, 2012)
This study was carried out to test for antinociceptive effect of the methanolic extract of ginger using acetic acid induced writhing in rats and compared to morphine and diclofenac sodium as standard drugs. The methanolic extract of ginger, showed dose dependent responses whereas 50 and 100mg/kg produced 100%protection against writhing  induced  by  acetic acid (0.6 %  i.p.) .  This protection supersedes the effect of diclofenac sodium (25, 50 and 75 mg/kg). On the other hand morphine (2.5- 10 mg/kg), exhibited 100% protection against writhing induced by acetic acid. Therefore we can conclude and recommend that, ginger is a potential source of new and effective anti-nociceptive agent(s). Bioassay guided fractionation for the methanolic extract of ginger should be investigated for the determination of active ingredient(s), and to elucidate their mechanism of action.  الخلاصة: أجريت هذ الدراسة  لإختبار تأثيرالخلاصة الميثانولية  للزنجبيل كمسكن للألم باستخدام حمض الاستيك الذي يحفز الانقباضات ألبطنيه المسببة للألم ومقارنته بالمورفين و الدايكلوفيناك صوديوم  كأدوية مرجعية. أظهر  المستخلص الميثانولي للزنجبيل إستجابات إعتمادا على  الجرعات حيث إنه في الجرعات  50 و 100مجم/كجم نتجت حماية بنسبة 100% ضد الانقباضات المسببة  بواسطة حمض الأسيتيك (0,6%)˛ حيث يعتبر أفضل تأثيرا من الدايكلوفيناك صوديوم (25، 50، 75مجم/كجم) ومن ناحية أخرى فإن المورفين (2.5 -10 مجم/كج) قد أعطى حماية بنسبة 100% ضد الانقباضات المسببه بواسطة حمض الأسيتيك.  لذا نستنتج   ونوصي بأن الزنجبيل مصدر متوقع  جديد فعال كمسكن للآلام. كما نوصي  بأن تجرى الاختبارات الحيوية الموجهه للتجزئة للزنجبيل لتحديد المادة الفعالة و توضيح آلية عملها.